DEMO-OCCUPATIONAL IMBALANCES IN ROMANIAN RURAL AREA – CENTER REGION - Chitea, Lorena (Economics of Agriculture, 2012)
Human resources are the main factor of development, regardless of the environment to which we relate – urban or rural. But, problems appear especially in rural communities, where the population faces a series of demographic, social and cultural problems - demographic decline, a low level of occupational diversification, reduced opportunities for recreation and literacy.